KONTEKSTUALISASI NILAI-NILAI LUHUR WARISAN LELUHUR DI ERA GLOBAL: BELAJAR DARI SERAT TRIPAMA DAN WAHYU MAKHUTA RAMA - Ahmad Salehudin (Religi: Jurnal Studi Agama-agama, 2017)
Heritage is a “blue print” that not only serves as guidance, but also a parameter for its heirs to live their lives. We must behave as we have "embodied" in the inheritance of the ancestors as they are. Heritage is often positioned as something that must not be changed, so changing it is considered inappropriate and immoral. Changing it can be considered as violating custom and destroying a taboo. Whereas if we look at the process of creation of ancestral heritage, then we will know that the creation of ancestral heritage tends to be accommodating and dynamic along with the times, such as the process of creating Serat Tripama and Wahyu Makhuta Rama. Through both of them, we know that the creation process of heritage is dynamic and accommodating.